Detection of Hemoglobin Constant Spring by Capillary Electrophoresis and High-performance Liquid Chromatography: A Study in Kelantan, Malay - Sumaiyah Adzahar; Nabilah Rameli; Suryati Hussin; Nik Fatma Fairuz Nik Mohd Hassan; Wan Norhasanah Wan Yusoff; Shafini Mohamed Yusoff; and Rosnah Bahar (Oman Medical Journal)
Objectives: Hemoglobin Constant Spring (Hb CS) is one of the most common non-deletion types of alpha (α) thalassemia in Southeast Asia. The nature of this abnormal globin gene is unstable, labile, and present in minute amounts in the peripheral blood, leading to underdiagnosis. This study aimed to determine the prevalence of Hb CS among the Kelantan population in Malaysia, compare the levels of Hb CS detected by capillary electrophoresis (CE) among three groups of Hb CS (heterozygous, homozygous, and compound heterozygous), and evaluate the efficacy of CE and high-performance liquid chromatography (HPLC) in detecting Hb CS. Methods: A cross-sectional study was conducted using data collected from secondary school students in Kelantan from 2017 to 2018 who participated in a thalassemia screening program conducted by the Ministry of Health, Malaysia. Hb analysis was performed using an automated CE system (CAPILLARYS 2 Flex-Piercing System Sebia) and HPLC (VARIANT II, Bio-rad Laboratories). DNA analysis was used multiplex polymerase chain reaction and multiplex amplification refractory mutation system to detect deletion and non-deletion α-thalassemia. Results: Termination codon CS mutation was confirmed among 376 (99.5%) samples with a peak value in zone 2 of CE. Heterozygous Hb CS was the most common type, detected in 344 samples (91.5%), followed by compound heterozygous Hb CS in 31 samples (8.2%) and one sample (0.3%) of homozygous Hb CS. Conclusions: The diagnosis of Hb CS is most accurately achieved by combining CE and HPLC methods, with confirmation by DNA molecular study, although the latter is more expensive.